Changthangi Pashmina Goat Genome: Sequencing, Assembly, and Annotation - Bhat, Basharat; Ganai, Nazir A.; Singh, Ashutosh; Mir, Rakeeb; Ahmad, Syed Mudasir; Majeed Zargar, Sajad; Malik, Firdose (Frontiers in Genetics, 2021)
Pashmina goats produce the world’s finest and the most costly animal fiber (Pashmina) with an average fineness of 11-13 microns and have more evolved mechanisms than any known goat breed around the globe. Despite the repute of Pashmina goat for producing the finest and most sought-after animal fibre, meager information is available in the public domain about Pashmina genomics and transcriptomics. Here we present a 2.94 GB genome sequence from a male Changthangi white Pashmina goat. We generated 294.8 GB (>100X coverage) of the whole-genome sequence using the Illumina HiSeq 2500 sequencer. All cleaned reads were mapped to the goat reference genome (2,922,813,246 bp) which covers 97.84% of the genome. The Unaligned reads were used for de novo assembly resulting in a total of 882 MB non-reference contigs. De novo assembly analysis presented in this study provides important insight into the adaptation of Pashmina goats to cold stress and helps enhance our understanding of this complex phenomenon. A comparison of the Pashmina goat genome with a wild goat genome revealed a total of 2823 high impact single nucleotide variations and small insertions and deletions, which may be associated with the evolution of Pashmina goats. The Pashmina goat genome sequence provided in this study may improve our understanding of complex traits found in Pashmina goats, such as annual fiber cycling, defense mechanism against hypoxic, survival secret in extremely cold conditions, and adaptation to a sparse diet. In addition, the genes identified from de novo assembly could be utilized in differentiating Pashmina fiber from other fibers to avoid falsification at marketing practices.